New Implantable Technologies Improve Prognosis of Patients With CHF - Kuznar, Wayne (MD Conference Express, 2015)
In advanced heart failure, patient prognosis is being influenced by new technologies in cardiovascular implantable electronic devices, including a totally subcutaneous implantable cardioverter defibrillator with an impressive complication-free rate, leadless cardiac pacing, and multiple-sensor ICDs that are better able to monitor heart failure status.